2021
DOI: 10.1002/anie.202102589
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Neutral S‐nitrosation Mediated by a Dicopper Center

Abstract: An unprecedented redox-neutral S-nitrosation of thiol has been achieved at dicopper(I,I) center. Treatment of dicopper (I,I) complex with excess NO • and thiol generates a dicopper (I,I) di-Snitrosothiol complex [Cu I Cu I (RSNO)2] 2+ or dicopper (I,I) mono-Snitrosothiol complex [Cu I Cu I (RSNO)] 2+ , which readily release RSNO in 88-94% yield. The S-nitrosation reaction proceeds through a mixedvalence [Cu II Cu III (-O)(-NO)] 2+ species, which deprotonates RS-H at the basic -O site and nitrosates the RS −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
(152 reference statements)
1
18
0
Order By: Relevance
“…Since 2 can deprotonate MeOH, it is reasonable to hypothesize that it can 4). [48] Scheme 5. Ap ossible mechanistic pathway to generate 3-PE from dicopper(II,III) m-oxo, m-nitrosyl 2.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2 can deprotonate MeOH, it is reasonable to hypothesize that it can 4). [48] Scheme 5. Ap ossible mechanistic pathway to generate 3-PE from dicopper(II,III) m-oxo, m-nitrosyl 2.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…The differences pectrum of 14 Nand 15 Nsample is shown in black. C) Solidstate structure of [LCu II Cu II (m-NO)(m-OMe)] complex 4.E llipsoids are set at 50 %p robability.T he outer-sphere triflate anion, solvent molecules, hydrogen atoms, and minor components of disordered atoms are omitted for clarity.S elected bond distances []: Cu1-N1 1.976(16), Cu2-N1 2.00(3), Cu1-O1 1.871(15), Cu2-O1 1.950(13), N1-O2 1.32-(5), N1B-O2B 1.27(4) [48].…”
mentioning
confidence: 99%
“…Recently, we demonstrated that a synthetic dicopper complex could promote S-nitrosation without an external oxidant, which serves as a functional model of ceruloplasmin-mediated NO • storage (Scheme 1C). 32,33 A common mechanistic step in metal-mediated S-nitrosation is the insertion of NO • into metal−thiolate bonds to generate RSNO together with the reduced metal center, 16,25,26,28 reminiscent of reductive elimination in organometallic chemistry. Therefore, it is commonly proposed that the coupling of NO • with thiol occurs at a transient metal nitrosyl…”
mentioning
confidence: 99%
“…To visualize the interconversion between M x (NO)(SR) and M x (RSNO), we employ our dicopper platform 33 which has successfully modeled the S-nitrosation process at ceruloplasmin. 22,23 Instead of using the previous Py 4 DMB ligand (Scheme 3 right), we prepared a new binucleating ligand L by linking four pyridines with a 2-hydroxybenzenethiol linker (Scheme 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation